Relationship Between Diet Patterns, Sleep Quality, and Nutritional Status Towards Anemia Incidence in Pregnant Women in The Work Area of Pulosari Community Health Center, Koranji Village, Pandeglang Regency, Banten in 2023 - Asni; Dahlan, Febry Mutiariami; Putri Azzahroh (Rajaki of Tulip Medika Publisher, 2025)
Background: Pregnancy is a very important period for the formation of the quality of human resources in the future, because the child's growth and development will be very much determined by the conditions when the fetus is in the womb. This is related to nutritional problems in pregnant women. One of the most common nutritional disorders and a major nutritional problem in Indonesia is anemia. Objective: The relationship between diet, sleep quality, and nutritional status on the incidence of anemia in pregnant women in the work area of the Pulosari Health Center, Koranji Village, Pandegalng Regency, Banten in 2023. Methodology: This study used an observational research type with a cross-sectional design. The sample in this study was 61 respondents, all pregnant women. Sampling used an accidental research instrument technique for dietary pattern variables using a food record sheet, sleep quality using the PSQI instrument, and for nutritional status using a questionnaire sheet in calculating LILA Data were analyzed using univariate and bivariate analyses with the chi-square statistical test. Results: The results of a univariate analysis of diet, sleep quality, and nutritional status in pregnant women showed that the majority of pregnant women were not anemic, 72.1% of pregnant women who had moderate eating patterns were 34.4%, and 24.6% had poor eating patterns. The results of the bivariate analysis show that the p-value after it is carried out is 0.000, so that the comparison results obtained are 0.000 <0.05. The quality of sleep is good several 49 pregnant women (80.3%), while the respondents who have not experienced a change or have less sleep quality by 12 pregnant women(19.7%). Analysis of nutritional status with a risk of 50.8% and nutritional status of pregnant women as normal as 49.2%. Conclusions: most pregnant women have good eating patterns, sleep quality, and nutritional status; most pregnant women experience no anemia; there is an influence of diet, sleep quality, and nutritional status on the incidence of anemia in pregnant women. It is expected that pregnant women can improve their diet, sleep quality, and nutritional status to prevent anemia.